GEOELECTRIC DETERMINATION OF THE GROUNDWATER POTENTIAL OF PARTS OF POMPO VILLAGE, MINNA, NIGERIA - Udensi, E. E., Chikwelu, E. E. (International Journal of Scientific Research and Management (IJSRM), 2013)
The Geoelectric determination of groundwater potential of parts of Pompo village opposite Federal University of Technology, Gidan Kwano Campus, Minna, was carried out using conventional Vertical Electrical Sounding (VES) and Self potential methods. The aim of this survey is to determining the ground water potential of the area and to locate those areas that could be useful for civil engineering workers. The data obtained were interpreted using computer-based program called Zohdy, which showed a laterally and vertical varying succession of high and low resistive geoelectric layers throughout the area. The resulting (Interpreted) models were used to produce regolith map and self potential contour maps. The aquifer system of the study area is generally characterized by relatively low resistivity value between 374Ωm and about 1800Ωm in the weathered basement and supported on some VES points by fractured basement and its thickness ranges from 3m to >20m. The most promising region of the site lies on west and south-eastern part, while the civil and the environmental works will be best located at the northern and southern part where the fresh basement is uplifted.